Innovative disruption in financial technology and payment systems - Chatterjee, Pushpalika (International Journal of Financial, Accounting, and Management, 2025)
Purpose: This study explores the transformative impact of financial technology (fintech) on the global financial services industry, focusing on innovations, regulatory implications, and challenges. The research aims to identify key technological disruptions, examine the regulatory landscape, and highlight opportunities and risks introduced by fintech. Methodology/approach: A Systematic Literature Review (SLR) was conducted using SCOPUS, IEEE Xplore, and ScienceDirect. Following a structured protocol, 153 peer-reviewed articles (2014–2019) were analysed through thematic and meta-analytical approaches. The study adopted an interpretative philosophy and used the PICOC framework to refine search precision and synthesis. Results/findings: The analysis reveals fintech’s disruptive innovations in financing and payment systems, such as peer-to-peer (P2P) lending, crowdfunding, blockchain-enabled transactions, and mobile payments. These services have enhanced financial inclusion, operational efficiency, and customer accessibility. Regulatory frameworks have evolved in parallel, though challenges remain in addressing moral hazard, cybersecurity, and compliance. Geographically, Asia, particularly China and Indonesia, leads fintech research and implementation. Conclusion: Fintech has significantly reshaped financial ecosystems by enabling decentralized financial services, accelerating digital transactions, and fostering inclusivity. However, cybersecurity risks, limited regulatory clarity, and uneven global adoption continue to impede its sustainable integration. Limitations: The study is limited to English-language literature from 2014–2019 and may not capture recent post-pandemic developments or region-specific innovations in Islamic or informal economies. Contribution: This paper contributes a comprehensive synthesis of fintech’s evolution, identifies existing gaps, and offers insights for policymakers, financial institutions, and researchers to foster a balanced, secure, and innovative financial environment.